The Role of Proteolytic Activity and Computational Studies on Protease Efficiency in Wound Healing - Ananta, Yorasakhi; Fitri, Salsabila Dwi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2024)
Microbial proteases play an important role in various medical applications, especially in the wound healing process. Their proteolytic activity allows the breakdown of proteins involved in the inflammatory process and tissue regeneration. This study aims to review the role of microbial proteolytic activity in wound healing and explore the application of computational studies to predict the effectiveness of proteases in wound therapy. Molecular modeling and in silico prediction are used to identify potential proteases that are efficient in improving wound healing. This study also includes an analysis of the mechanism of action of proteases on biological molecules in wounds, as well as the challenges and prospects of using microbial proteases in modern medical therapy.